Narrowband imaging (NBI): a literature review of its usefulness in laryngology - Esper Zamar, Claudia; Sala, Federico; Magaró, Manuel M. (Revista del Hospital Italiano de Buenos Aires, 2025)
Introduction: Imagine the possibility of achieving an accurate etiological diagnosis, almost comparable to the histopathological result, but with our own eyes. This is how the term optical biopsy was introduced, referring to the diagnostic precision of the narrow band imaging (NBI) light filter when assessing lesions of the upper aerodigestive mucosa. The morbidity and mortality of laryngeal cancer decrease when the tumor is detected and treated early. Our objective is to analyze the results obtained regarding the sensitivity and specificity of the NBI filter for detecting early laryngeal lesions in studies published between 2011 and 2021. As secondary objectives, we will assess the role of NBI in the intraoperative setting and the validated classifications for applying this technology.State of the art: The mean sensitivity of the NBI found for premalignant lesions in this analysis was 88% compared to white light (WL), which was 78.4%. The mean specificity was 81.4% compared to WL, which was 68.7%. The variation in sensitivity of NBI vs. WL was 13.8% and specificity was 13.6%. Regarding the evaluation after chemoradiation treatment, Piazza et al. establish that NBI allows 20% more detection of persistence or recurrence than classic endoscopies.Discussion: Narrow Band Imaging (NBI) significantly enhances the early detection of malignant and recurrent laryngeal lesions, surpassing the sensitivity of conventional white light. Its systematic use optimizes diagnostic interpretation, reduces unnecessary biopsies, and improves surgical margin delineation, even in in-office procedures. Although it does not replace histopathological evaluation, NBI is a key tool that increases diagnostic accuracy and oncologic safety. Two validated classifications exist: the Ni classification and that of the European Laryngological Society (ELS).Conclusion: NBI is established as an essential tool for the early detection and accurate assessment of laryngeal lesions, improving both diagnostic and surgical safety. Although it does not replace histopathological analysis, it significantly enhances clinical decision-making and reduces invasive procedures.
Keywords: narrow band imaging; early laryngeal cancer; laryngeal endoscopy